2016
DOI: 10.1111/mec.13795
|View full text |Cite
|
Sign up to set email alerts
|

Investigating genomic and phenotypic parallelism between piscivorous and planktivorous lake trout (Salvelinus namaycush) ecotypes by means ofRADseq and morphometrics analyses

Abstract: Repeated adaptive ecological diversification has commonly been reported in fish and has often been associated with trophic niche diversity. The main goal of this study was to investigate the extent of parallelism in the genomic and phenotypic divergence between piscivorous and planktivorous lake trout ecotypes from Laurentian Shield lakes, Canada. This was achieved by documenting the extent of morphological differentiation using geometric morphometrics and linear measurements as well as the pattern of genomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 167 publications
(339 reference statements)
3
51
0
Order By: Relevance
“…For the TRT dataset, M5 was the most suitable value for identifying polymorphism, and this is considerably higher than M2 as most commonly used in salmonid RAD‐seq studies (Lemay & Russello ; Bernatchez et al . ) and in other teleost species (Catchen et al . ; Martin & Feinstein ; Fowler & Buonaccorsi ).…”
Section: Discussionmentioning
confidence: 98%
“…For the TRT dataset, M5 was the most suitable value for identifying polymorphism, and this is considerably higher than M2 as most commonly used in salmonid RAD‐seq studies (Lemay & Russello ; Bernatchez et al . ) and in other teleost species (Catchen et al . ; Martin & Feinstein ; Fowler & Buonaccorsi ).…”
Section: Discussionmentioning
confidence: 98%
“…The minimal overlap and difference in numbers of SNPs identified between F ST outlier approaches identified may indicate different sensitivities of each approach to the effects of genetic drift and structure. Notably, studies comparing outflank and bayescan have found little overlap between the approaches (e.g., Bernatchez, Laporte, Perrier, Sirois, & Bernatchez, ; Chen, Farrell, Matala, & Narum, ; Micheletti, Matala, Matala, & Narum, ). The significant SNP associations using EAA were unique to each environmental variable in 41%–79% of cases (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…One of the most diversely polymorphic species is the lake trout, which exhibits two to four morphs in at least five lakes, differentiated by their trophic specialization, habitat occupancy and mechanism of buoyancy regulation. Lake trout morphs most commonly emerge in large lakes where they become piscivorous or invertivorous and occupy shallow or deep habitats (Muir, Hansen, Bronte, & Krueger, ), indicating multiple parallel evolutionary events (Bernatchez, Laporte, Perrier, Sirois, & Bernatchez, ). A shallow‐water piscivorous form, referred to as the “lean” morph, is slim‐bodied with low lipid content, strongly contrasting with the “fat” morph or “siscowet,” a deep‐water piscivore that is deep‐bodied, high in lipids and consumes different fish species (Hansen et al., ; Ray, Hrabik, & Ebener, ; Zimmerman, Krueger, & Eshenroder, ).…”
Section: Interspecific Comparisonsmentioning
confidence: 99%